Early identification of frailty: Developing an international delphi consensus on pre-frailty. (March 2022) - Sezgin, Duygu; O'Donovan, Mark; Woo, Jean; Bandeen-Roche, Karen; Liotta, Giuseppe; Fairhall, Nicola; Rodríguez-Laso, Angel; Apóstolo, João; Clarnette, Roger; Holland, Carol; Roller-Wirnsberger, Regina; Illario, Maddalena; et al.
Highlights: Given the growing importance of the early identification of frailty to prevent subsequent functional decline and disability at both individual and population-level, we have conducted an international delphi study to identify defining characteristics of pre-frailty. The final consensus statement produced by this international collaboration of experts in the field describes pre-frailty as an aged-associated,  multi-factorial, multi-dimensional, and non-linear prodromal risk-state associated with one or more of physical impairment, cognitive decline, nutritional deficiencies, and socioeconomic inequalities, predisposing to the development of frailty. Further study is required to fully operationalise this definition of pre-frailty for use in clinical practice including the development of improved screening and assessment tools. Abstract: Background: : Frailty is associated with a prodromal stage called pre-frailty, a potentially reversible and highly prevalent intermediate state before frailty becomes established. Despite being widely-used in the literature and increasingly in clinical practice, it is poorly understood. Objective: : To establish consensus on the construct and approaches to diagnose and manage pre-frailty. Methods: : We conducted a modified (electronic, two-round) Delphi consensus study. The questionnaire included statements concerning the concept, aspects and causes, types, mechanism, assessment, consequences, prevention and management of pre-frailty. Qualitative and quantitative analysis methods were employed. An agreement level of 70% was applied. Results: : Twenty-three experts with different backgrounds from 12 countries participated. In total, 70 statements were circulated in Round 1. Of these, 52.8% were accepted. Following comments, 51 statements were re-circulated in Round 2 and 92.1% were accepted. It was agreed that physical and non-physical factors including psychological and social capacity are involved in the development of pre-frailty, potentially adversely affecting health and health-related quality of life. Experts considered pre-frailty to be an age-associated multi-factorial, multi-dimensional, and non-linear process that does not inevitably lead to frailty. It can be reversed or attenuated by targeted interventions. Brief, feasible, and validated tools and multidimensional assessment are recommended to identify pre-frailty. Conclusions: : Consensus suggests that pre-frailty lies along the frailty continuum. It is a multidimensional risk-state associated with one or more of physical impairment, cognitive decline, nutritional deficiencies and socioeconomic disadvantages, predisposing to the development of frailty. More research is needed to agree an operational definition and optimal management strategies.